Reconciling Researching and Teaching: Identity Tensions of Novice Nontraditional Language Teacher Educators Toward Professional Legitimacy - Gümüşok, Fatma; Balıkçı, Gözde; Başaran Uysal, Banu Çiçek (John Wiley and Sons Inc, 2026)
In this study, we, as novice nontraditional language teacher educators from Türkiye, present the sources and resolution of professional identity tensions we experienced toward professional legitimacy in the field of TESOL in our initial years of service. The theoretical framework underpinning our research is grounded in professional legitimacy and identity tensions. We aim to focus on a central facet of our identity journey: the pursuit of legitimacy, interwoven with tensions. This study investigates the pivotal role of these tensions as they shape critical moments in establishing professional legitimacy. Employing the collaborative autoethnographic methodology, we analyze our experiences over five academic semesters, allowing for an in-depth exploration of our personal and professional narratives. We reflect on our challenges and successes in both teaching and research, providing a comprehensive view of our journey as TESOL educators. Our narratives revealed how we positioned ourselves as nontraditional teacher educators and novice researchers who strive for high-impact research by reconciling the emerging tensions in both. This process of reflecting on our internal tensions helps us to discover our in-depth beliefs and identities and proves the potential value of collaborative autoethnography in providing a platform for teacher educators to develop and grow together. © 2025 TESOL International Association.
Keywords: collaborative autoethnography; identity development; legitimacy; nontraditional teacher educators; positioning; tensions